Obstetrical Management of Hydrocephalic Fetal Monster in a Tharparker Cow: A Case Report - G, Sasi; Kumar, Pramod; Kumar, Tapendra; Bhalothia, Shivendra Kumar (Indian Journal of Veterinary Sciences and Biotechnology, 2020)
Hydrocephalus condition is described either as an external or an internal. In the external hydrocephalus (Vidya Sagaret al., 2010), fluid accumulates in the subarachnoid space exterior to the brain, whereas in the internal hydrocephalusfluid accumulates in the ventricles of the brain.